2017
DOI: 10.1128/jvi.00048-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Functions for Hepatitis C Virus Envelope Glycoprotein E1 in Virus Entry and Assembly

Abstract: Hepatitis C virus (HCV) envelope glycoprotein complex is composed of E1 and E2 subunits. E2 is the receptor-binding protein as well as the major target of neutralizing antibodies, whereas the functions of E1 remain poorly defined. Here, we took advantage of the recently published structure of the N-terminal region of the E1 ectodomain to interrogate the functions of this glycoprotein by mutating residues within this 79-amino-acid region in the context of an infectious clone. The phenotypes of the mutants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 60 publications
5
40
0
Order By: Relevance
“…The first hydrophobic region of E1 has previously been implicated in viral particle production, and several amino acids within this region are important for viral infectivity [47, 48]. Additionally, one specific E1 mutation, D263A (E1 aa71), attenuated viral infectivity and resulted in secreted Core protein but not HCV RNA [48]. Taken together with our findings that NS4A binds to the E1 the hydrophobic region, which contains aaD263, we hypothesized that Y45F may have a similar phenotype as the E1 D263A mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first hydrophobic region of E1 has previously been implicated in viral particle production, and several amino acids within this region are important for viral infectivity [47, 48]. Additionally, one specific E1 mutation, D263A (E1 aa71), attenuated viral infectivity and resulted in secreted Core protein but not HCV RNA [48]. Taken together with our findings that NS4A binds to the E1 the hydrophobic region, which contains aaD263, we hypothesized that Y45F may have a similar phenotype as the E1 D263A mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we found that NS4A binds to E1 and that antagonizing this interaction with one amino acid change in NS4A prevents viral envelopment. We mapped the binding site of NS4A on E1 and found that it interacts with the first hydrophobic region, a region that is known to be important for viral particle production [47, 48]. Finally, we found that the Y45F mutation in NS4A, which prevents envelopment, also results in secretion of noninfectious, incompletely formed virions that are composed of low density Core protein oligomers that lack HCV RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting analyses were performed as described previously (31). Briefly, supernatants and lysates of wt and mt PLC3/HEV-p6 cells were heated for 20 min at 80°C in the presence of Laemmli buffer (reducing or non-reducing).…”
Section: Methodsmentioning
confidence: 99%
“…It is also the main target for the host's adaptive immune system. Recently the E1 protein was also shown to be involved in viral entry and virion assembly (Haddad et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of multiple in vitro systems as well as experimental animal models, little is still known about the structure and actual function of the E1 glycoprotein (Douam et al, 2014; Haddad et al, 2017; Lavillette et al, 2007; Wahid et al, 2013). Evidence for the immunogenicity and the induction of neutralizing antibodies by E1 has been reported.…”
Section: Introductionmentioning
confidence: 99%